2020
DOI: 10.1093/rheumatology/keaa098
|View full text |Cite
|
Sign up to set email alerts
|

Association between depression and anxiety with skin and musculoskeletal clinical phenotypes in systemic lupus erythematosus

Abstract: Objectives To study the clinical phenotypes, determined based on cumulative disease activity manifestations, and sociodemographic factors associated with depression and anxiety in SLE. Methods Patients attending a single centre were assessed for depression and anxiety. SLE clinical phenotypes were based on the organ systems of cumulative 10-year SLE Disease Activity Index 2000 (SLEDAI-2K), prior to visit. Multivariable logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 44 publications
3
27
0
1
Order By: Relevance
“…Among inflammatory phenotypes characterizing patients with depression and anxiety, the patients have autoimmune diseases to be at high risk (4,32,33). In particular, SLE patients with anxiety and depression have specificity disease phenotypes that involve multiple organs (34). This supports one point at least, that in SLE patients with anxiety, the management of depression, fatigue, and anxiety may not only be a separate entity but a whole way of looking at treatment better.…”
Section: Discussionmentioning
confidence: 84%
“…Among inflammatory phenotypes characterizing patients with depression and anxiety, the patients have autoimmune diseases to be at high risk (4,32,33). In particular, SLE patients with anxiety and depression have specificity disease phenotypes that involve multiple organs (34). This supports one point at least, that in SLE patients with anxiety, the management of depression, fatigue, and anxiety may not only be a separate entity but a whole way of looking at treatment better.…”
Section: Discussionmentioning
confidence: 84%
“…However, Eldeiry found a significant association in female LES patients who experienced skin discoloration compared to those who did not. 27 Jordan et al also found reduced quality of life in LES sufferers which led them to become depressed, so that mental assistance from family and those around them is urgently needed. 28 In this study, the number of research subjects was Correlation analysis was used to assess the strength of correlation and its direction.…”
Section: Resultsmentioning
confidence: 99%
“…27 These include: skin (skin rash, alopecia and mucosal ulcers), central nervous system (seizure, psychosis, organic brain syndrome, cranial nerve involvement, visual disturbance, lupus headache, cerebrovascular accident), vasculitis, musculoskeletal (arthritis and myositis), renal (proteinuria, hematuria, pyuria and urinary casts), serosal (pleuritis and pericarditis), hematological (leukopenia and thrombocytopenia), immunological (low complements and positive anti-dsDNA antibodies), and constitutional (fever). 28 Ten-year cumulative organ damage was quantified using Systemic Lupus International Collaborating Clinics (SLICC)/ACR Damage Index (SDI) which were ascertained by 12 organ-systems. 25,29…”
Section: Methodsmentioning
confidence: 99%
“…31 Ten-year cumulative organ involvement and damage by organ system, glucocorticoid use and presence of fibromyalgia (diagnosed based on the ACR 1990 fibromyalgia classification criteria). 28 Cumulative glucocorticoid use was calculated by determining the start and end date of each dose range, multiplying the time interval by the dose received and subsequently finding the sum dose of treatment periods.…”
Section: Methodsmentioning
confidence: 99%